Rengalin, a Novel Drug for Treatment of Cough in Children. Intermediate Data on Multicentre, Comparative Randomized Clinical Trial - N. A. Geppe; E. G. Kondyurina; A. N. Galustyan; T. E. Pak; N. B. Baltserovich; O. V. Zhiglinskaya; A. V. Kamaev; S. G. Lazareva; S. L. Laleko; I. M. Melnikova; E. V. Mikhailova; O. A. Perminova; et al. (Антибиотики и Химиотерапия)
Rengalin liquid formulation on the basis of antibodies to bradlkinin histamine and morphine was specially designed for the treatment of cough in children. The three-component combination in therapeutically active against both dry and wet cough due to effect on diverse pathogenetic aspects of the cough reflex. The aim of the multicenter, comparative, randomized clinical trial was to estimate the efficacy and safety of rengalin in the treatment of cough in patients with acute respiratory infection (ARI) of the upper respiratory tract. Methods. One hundred forty six patients at the age of 3 to 17 years (the average age of 8.2+3.6 years) from 14 medical centres of Russia were observed. The patients sufferedfrom dry/nonproductive, frequent, sore cough preventing from day-time activity and/or night sleep (>4 by the Cough Severity Scale). The cough duration ranged from 12 hours to 3 days. For 3 days the patients of group 1 (n=71) and group 2 (n=75) were treated with rengalin and sinekod (butamirate) respectively. For the following 4 days the patients (in case of viscid expectoration were treated with ambroxole in the age doses. The results of the Per Protokol Analysis (n=67 rengalin group and n=73 sinekod group) with an account of the Non-Infectiority Design are presented. Results. In 3 days the number of the group 1 patients with significant improvement/recovery by the day and night estimates amounted to 90% and 88% respectively (vs. 81% and 88% in the group 2 patients, no night opisodes of cough after 3-days rengalin use being recorded in 52% of the patients vs. 34% in the sinekod group patients (p=0.0003). On the 7th day of the treatment with rengalin the number of the children with significant improvement of or recovery from day-time cought amounted to 99%and that of the patients with significant improvement of or recovery from night-time cough amounted to 93%, in 90% of them no night-time cough being recorded (p=0.0008). As for the patients of the reference group, the respective values were 93% and 90%, no night-time cough being recorded in 81% of the patients. The time required for development of productive/moist cough during the 3-day treatment course in the patients of both the group was the same (2.9+0.3 days in the patients of group 1 and 2.9+0.4 days in the group 2 patients. Moreover, in 34% of the rengalin dry cough became residual (as rare episode of tussiculation with scantly exudation). After 3-day course of the rengalin therapy, 66% of the patients was treated with ambroxole (versus 95% in sinecod group (p0.0001 by the results of the frequency analysis). The total duration of cough in the patients of groups 1 and 2 was 6.5±0.8 and 6.7±0.7 days respectively (the comparability truth, p=0.0001). The severity of the day-time cough by the area under the curve estimates for 7 days of the treatment in the rengalin group patients was equel to 14.3+5.6 numbers - days and that of the patients of the sinekod® group was equal to 15.9±6.1 numbers - days. The severity of the night-time cough was equal to 4.2+2.7 number - days respectively. In 2 patients (3%) treated with sinekod® signs of ARI generalization was observed after the 3-day treatment (p>0.0001). The research physicians-investigators (CGI-EL Scale) the combination of the anti- and protussive activities in one drug to be efficient and absolutely safe for the chilgren. The therapeutic efficacy in the patients of the rengalin group was higher in 3 days (2.1±0.5 numbers) and even in 7 days (2.7±0.5 numbers). The results value in the patients of the sinekod® group being 1.8±0.4 and 2.5±0.6 numbers (one-way ANOVA for repeated estimates ANOVA: Visit - F1/138=146, p